2019
DOI: 10.1016/j.preteyeres.2019.05.005
|View full text |Cite|
|
Sign up to set email alerts
|

Conservative management of retinoblastoma: Challenging orthodoxy without compromising the state of metastatic grace. “Alive, with good vision and no comorbidity”

Abstract: Retinoblastoma is lethal by metastasis if left untreated, so the primary goal of therapy is to preserve life, with ocular survival, visual preservation and quality of life as secondary aims. Historically, enucleation was the first successful therapeutic approach to decrease mortality, followed over 100 years ago by the first eye salvage attempts with radiotherapy. This led to the empiric delineation of a window for conservative management subject to a "state of metastatic grace" never to be violated. Over the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
157
1
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 164 publications
(193 citation statements)
references
References 575 publications
(827 reference statements)
0
157
1
9
Order By: Relevance
“…The most common early symptom is leukocoria, followed by strabismus. There are multiple treatment options, of which the most used currently is the more eye conservative ones, chemotherapy in situ, in detriment of systemic chemotherapy, radiotherapy and eye enucleation [33]. Yu et al found than the activation of c-Jun N-terminal kinase (JNK) and p38 MAPK on the retinoblastoma Y79 cell line was induced by curcumin.…”
Section: Eye Antitumor Activity (Retinal and Choroidal Tumors)mentioning
confidence: 99%
“…The most common early symptom is leukocoria, followed by strabismus. There are multiple treatment options, of which the most used currently is the more eye conservative ones, chemotherapy in situ, in detriment of systemic chemotherapy, radiotherapy and eye enucleation [33]. Yu et al found than the activation of c-Jun N-terminal kinase (JNK) and p38 MAPK on the retinoblastoma Y79 cell line was induced by curcumin.…”
Section: Eye Antitumor Activity (Retinal and Choroidal Tumors)mentioning
confidence: 99%
“…Additionally, any suggestion of optic nerve enlargement or enhancement on MRI scanning mediates enucleation with attention to resecting the fullest possible extent. Conservative therapy for retinoblastoma in an attempt to save the eye(s) is most often done with chemotherapy, either as 3-drug intravenous or single/multi-agent intra-arterial chemotherapy [12,[27][28][29]. Either regimen often requires consolidation with other localized therapies including red or green laser therapy, cryotherapy, intravitreal chemotherapy for tumor seeding in the vitreous, or brachytherapy for localized tumors.…”
Section: Retinoblastoma Therapymentioning
confidence: 99%
“…Usually diagnosed in children under the age of three [9], RB comprises an important subject in cancer genetics research due to its distinct association with the RB1 tumor suppressor gene. While the majority of RB cases are caused by sporadic somatic mutations of the gene, upwards of 40% of patients are affected by a heritable form of the disease that usually affects both eyes and can lead to a host of other systemic malignancies [8,[10][11][12][13]. In order to decipher the specific subtype (heritable versus non-heritable) of RB in presenting patients and their families, genetic testing of the peripheral blood to determine the presence of a germline mutation is an essential component in the management and counseling of these patients [14].…”
Section: Introductionmentioning
confidence: 99%
“…1 Advances in chemotherapy and local treatment have resulted in improved globe salvage and reductions in disease-specific mortality. [4][5][6] Toward that end, multi-specialty management, international outreach and cooperative research are crucial. 2,3,[5][6][7][8][9][10][11][12][13][14][15] Despite new retinoblastoma treatment strategies, ever-widening disparities persist with respect to access to subspecialty care, globe salvage and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29][30] Mortality rates have been so low in HIC that the focus of ophthalmic oncology care has shifted from metastasis to globe salvage, visual rehabilitation and quality of life. 4 This is not the case for low-resource countries, where children with retinoblastoma have been more likely to lose their eye and die of metastatic disease. 2,31,32 Low resource countries suffer from a lack of retinoblastoma awareness, trained ophthalmic oncologists, pathologists and genetic services.…”
Section: Introductionmentioning
confidence: 99%